CURRENT STATE OF FORMATION OF READYNESS OF PRIMARY PRIMARY SCHOOL TEACHERS FOR INTRODUCTION OF TECHNOLOGIES OF INTERACTIVE LEARNING IN THE PROFESSIONAL PROFESSIONAL - Rybak, Olga (Educological discourse, 2021)
The article considers topical issues of the current state of readiness of future primary school teachers to implement interactive learning technologies in professional activities at the present stage of reforming the education system, which is interpreted as: readiness to develop plans and goals, development of professional qualities of teachers, expanding the mobilization of psychological point of view, increasing the level of independence and responsibility to society. The essence of the concept of "readiness" for future primary school teachers is revealed. The place of such scientists is shown: A. Aleksyuk, N. Boltenkov, V. Bondar, O. Voloshenko, S. Garkusha, M. Dyachenko, I. Zyazyuna, N. Kichuk, O. Kiyashko, L. Krasyuk, N. Kuzmina, Z. Kurland, I. Kushakova, A. Linenko, O. Moroz, S. Nikitchina, S. Sysoeva, V. Slastyonina, S. Smirnova, L. Khomich, V. Chaika, I. Shaposhnikova, O. Yaroshenko, who studied the problems readiness of teachers in professional activity. The essence of the concept of readiness as a set of properties and qualities of the teacher’s personality, which determines the adaptation of a graduate of a higher education institution to the conditions of pedagogical work, is revealed. The development of research of scientists of readiness of primary school teachers for introduction of technologies of interactive training in professional activity is shown. The study analyzes the results of a survey of primary school teachers in Lviv, Lviv and Volyn regions on the use of interactive learning technologies. The level of use of interactive exercises at different stages of the lesson is shown, the sufficient level of use of technologies of interactive training of teachers of SZSh№ 68, Lviv. The best level of equipment of the technical base of schools in the conditions of development of the new Ukrainian school is determined. The place of a modern specialist who promotes the expansion of a positive level of learning with a willingness to implement technologies of interactive learning in professional activities is described.